A cross sectional study on musculoskeletal discomfort and its determinants among agricultural workers in a rural community of Tamil Nadu - Ramanathan, Parthasarathi; Prabhakar, Ram; Ananthan, Velmurugan Anbu (International Journal Of Community Medicine And Public Health, 2020)
Background: Musculoskeletal disorders are the major contributors of disability worldwide. So, the aim of the present study was to estimate the magnitude and the determinants of musculoskeletal discomfort among agricultural workers in a rural area of Tamil Nadu. Methods: A cross-sectional community-based study was conducted among 110 subjects aged 15 years and above residing in Veerapandi village, Theni, Tamil Nadu from July to December 2018. A structured questionnaire incorporating nordic musculoskeletal questionnaire was used to collect data. The prevalence of musculoskeletal discomfort (MSD) and its determinants were the main outcome variables. It was analysed with Epi info statistical software. Bivariate and multivariate analysis were done keeping p value<0.05 as statistically significant. Results: The mean age of the study population was 39.37±12.75 years. Majority (38.2%) were between 25 to 34 years. 54.5% were feamles. The prevalence of MSD was 63.6% (95% C.I. of 53.9% to 72.6%). Lower back (48.5%) was the most common site of MSD followed by knees (45.75%) and neck (35.7%). In bivariate and multivariate analysis, age, female gender and obesity (BMI ≥25 kg/m2) were the statistically significant determinants of MSD in the study population. Conclusions: The prevalence of MSD was very high in the study population. There is a pressing need for introduction of lifestyle modifications in high‐risk groups and initiate rehabilitative measures for those affected.